2020
DOI: 10.1093/jmcb/mjaa009
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulation of islet homeostasis and adaptation

Abstract: The islet of Langerhans produces endocrine hormones to regulate glucose homeostasis. The normal function of the islet relies on the homeostatic regulations of cellular composition and cell–cell interactions within the islet microenvironment. Immune cells populate the islet during embryonic development and participate in islet organogenesis and function. In obesity, a low-grade inflammation manifests in multiple organs, including pancreatic islets. Obesity-associated islet inflammation is evident in both animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 114 publications
1
9
0
Order By: Relevance
“…performed an analysis of single-cell data on human pancreas and found that monocytes and CD8+ T cells are enriched in the T2D pancreas ( 97 ). Our results are consistent with previous reports that monocytes and macrophages are the primary immune cell subsets that contribute to islet inflammation during T2D development ( 98 ). We also found correlations between the 17 pyroptosis-related hub genes and 13 immune cell types.…”
Section: Discussionsupporting
confidence: 94%
“…performed an analysis of single-cell data on human pancreas and found that monocytes and CD8+ T cells are enriched in the T2D pancreas ( 97 ). Our results are consistent with previous reports that monocytes and macrophages are the primary immune cell subsets that contribute to islet inflammation during T2D development ( 98 ). We also found correlations between the 17 pyroptosis-related hub genes and 13 immune cell types.…”
Section: Discussionsupporting
confidence: 94%
“…It is known that function of pancreatic β cells is gradually impaired by excessive glucose (glucotoxicity) and fatty acids (lipotoxicity) under the context of obese T2DM (Shao et al 2014 ). Additionally, obesity-associated systemic low-grade inflammation could cause an elevation of inflammatory cytokines and chemokines in circulation together with the accumulation and impaired function of various immune cells including macrophages and B cells in pancreas, resulting in islet inflammation and β-cell dysfunction (Eguchi et al 2017 ; Guo et al 2020 ; Ying et al 2019 ). Consistently, our current study observed decreased HOMA-β and increased insulitis as the progress of diabetes in db/db mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is also impaired in T2D [ 81 ]. Tissue-resident macrophages are known to play an important role in normal islets and in disease [ 82 ]. They can be important for beta cell proliferation, homeostasis, and function [ 83 ].…”
Section: Further Stepsmentioning
confidence: 99%